Conditioning with Lime and Fertilizer Improves Ionic Rare Earth Mine Tailings - Qin Zhang; Dongmei Shen; Jie Luo; Guanyue Wan; Caiyun Zhou; Xiaomin Zhao (Adsorption Science & Technology, 2021)
To explore rare earth mine tailings improvement technology without soil dressing, we planted Chinese cabbage in pots to determine the effect of different amounts of lime combined with fertilizer on the improvement of ionic rare earth mine tailings, aiming to provide a scientific basis for the reclamation of abandoned ionic rare earth mines. The results showed that the soil substrate of the tested rare earth tailings exhibited four forms of degradation: soil acidification, soil desertification, nutrient depletion, and heavy metal contamination by rare earth elements (REEs). The application of fertilizer alone (CK treatment) did not support Chinese cabbage growth, whereas different amounts of lime combined with fertilizer supported plant growth and significantly reduced the activity of the rare earth heavy metals. The height, fresh weight, and REE content of the Chinese cabbage plants were significantly reduced with an increase in the amount of lime applied. Addition of lime not only significantly improved the soil pore space and reduced soil acidification but also significantly increased the soil nutrient content. Our findings suggest that lime combined with fertilizer can improve ionic rare earth mine tailing soil degradation, thus promoting plant growth and achieving the improvement of ionic rare earth mine tailings without soil dressing.